2018
DOI: 10.1186/s40691-018-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tannin mordanting on coloring and functionalities of wool fabrics dyed with spent coffee grounds

Abstract: Coffee is the most widely consumed beverage in the world, with 7.4 million tons of coffee beans produced and distributed annually. It also takes up the second-highest trade volume after petroleum, implying its critical role in the economy (Jo et al. 2017). Coffee consumption by Koreans has been increasing continuously and, according to 2017 statistics, the annual coffee consumption by an average Korean adult has reached approximately 512 cups. According to the Korea Customs Service and the coffee industry, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…This is because the new bands were more intense after mordanting with tannic acid, as shown in Figure 3. Tannin is very soluble in water, and the hydrolyzable tannins break down via hydrolysis to give gallic acid, a type of phenolic compound [15,16,17]. Therefore, a significant amount of phenolic compounds was chemically attached to the wool fibers through the mordanting process as well.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the new bands were more intense after mordanting with tannic acid, as shown in Figure 3. Tannin is very soluble in water, and the hydrolyzable tannins break down via hydrolysis to give gallic acid, a type of phenolic compound [15,16,17]. Therefore, a significant amount of phenolic compounds was chemically attached to the wool fibers through the mordanting process as well.…”
Section: Resultsmentioning
confidence: 99%
“…Like in the case of quaternary ammonium compounds, functional antimicrobial property of mixture of chitosan and silver nanoparticles has been reported by researchers to be better than that of individual agent. Therefore, coating textile fibers with mixture of chitosan and silver nanoparticles imparts very good antimicrobial property onto them [4]. Chitosan or chitosan/Ag + coated textile materials are very good as surgical garments, gloves and face masks.…”
Section: Chitosanmentioning
confidence: 99%
“…Bhuiyan et al [3] reported Lawsonia inermis L dyed jute fabric to have a good microbial inhibition and when surface modified with chitosan the percentage inhibition greatly improved. Hong [4] observed that tannin mordanted spent coffee grounds dyed wool fabric inhibited above 95% of microbial growth. Jabar et al [1] reported that 1, 3-bis[(furan-2-l) methylene]thiourea functional dyed wool and cotton fabrics have excellent fungi inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…Tannins are generally divided into two groups (Figures 8 and 9): Functional Properties of Natural Dyed Textiles DOI: http://dx.doi.org /10.5772/intechopen.88933 Tannin is considered as a protective agent against microbes and UV rays. Antimicrobial and antioxidant properties of dyed wool fabric were observed to have improved after application of tannin [90].…”
Section: Tanninsmentioning
confidence: 99%